Therapeutic implications of chemokine-mediated pathways in atherosclerosis: realistic perspectives and utopias - Apostolakis Stavros; Amanatidou Virginia; Spandidos Demetrios A (Acta Pharmacologica Sinica, 2016)
Current perspectives on the pathogenesis of atherosclerosis strongly support the involvement of inflammatory mediators in the establishment and progression of atherosclerostic lesions. Chemokine-mediated mechanisms are potent regulators of such processes by orchestrating the interactions of inflammatory cellular components of the peripheral blood with cellular components of the arterial wall. The increasing evidence supporting the role of chemokine pathways in atherosclerosis renders chemokine ligands and their receptors potential therapeutic targets. In the following review, we aim to highlight the special structural and functional features of chemokines and their receptors in respect to their roles in atherosclerosis, and examine to what extent available data can be applied in disease management practices.